Cross-cultural analysis of consumer social media engagement - Khadzhibiekova, Aida; Brunet-Thornton, Richard; Jirsák, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
This paper aims to improve understanding of cultural differences in engagement with the brand’s social media pages on different platforms and analyze different perspectives on the key areas of social media engagement and social media advertising. In the theoretical part, the author aims to identify social media platforms, define social media use motivations and motivations for content engagement. The further author investigates the cross-cultural impact of social media on consumer behavior and describes cultural values and practices in researched countries. The results of the L'Oréal brand social media pages analysis made with the Socialbakers suite are presented in the practical part of this paper and are discussed in relation to the cross-cultural differences, in order to help to relate the theoretical findings to findings obtained from the tool.
Vedoucí práce: Richard Brunet-Thornton
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses